Effects of COH on the expression of connexin43 in endometrial stromal cells - Guolin Liu; Yuanyuan Tang; Yibing Han; Xiaoming Teng (Elsevier, 2019)
Objective: The purpose of this study was to investigate the effect of controlled ovarian hyperstimulation (COH) on gap junction, and to induce the effect of an estrogen level overdose on gap junction in vitro by COH. Here, we mainly focus on connexion43 (Cx43), progesterone receptor (PR) and prolactin-related protein (PRP), and CyclinD3 genes expression, as well as the expression of Cx43 protein, were investigated. Materials and methods: Mature BDF-1 mice were divided into different COH, and the mouse uterus was isolated, Paraffin sections evaluate the effect of COH on mouse uterine endometrial morphology. The other part was used for the extraction of mouse uterine endometrial stromal cells (ESC), some related gene changes are detected. Human ESC were isolated from human endometrium by primary culture, the estrogen concentrations 10−6 mol/L, 10−7 mol/L were added, the changes of Cx43 gene and related proteins were detected, too. Results: (1) HE staining showed that in the ovulatory endometrium of mice in the high super ovulation group, uterine glands in the stromal layer were significantly increased, the relative vascular tissues was less abundant. (2) In three groups of COH mice, the expression of Cx43, PR, and PRP genes in ESC was significantly different (P < 0.05). (3) In vitro ESC in the COH group showed significant differences in Cx43, PR, and CyclinD3 gene expression (P < 0.05), and showed an obvious dose effect. In addition, Western blot analysis showed that the Cx43 protein and Cx43 gene expression were similar. Conclusions: (1) Animal experiments study showed that Cx43 gene expression in ESC was significantly decreased in hyper COH, in addition, the advance in gene expression was significantly earlier, suggesting decidualization appeared significantly earlier. (2) In vitro COH demonstrated when the estrogen concentration used was higher, the expression level of Cx43 gene and protein was lower. Combined with animal experiments, the endometrium decidualization was advanced in mice that were underwent hyper COH, which may reflect the endometrial receptivity. Keywords: Connexin43, COH, Endometrial receptivity, Endometrial stromal cell